Frequency of Brushing and Use of Fluoridated Toothpaste in Children Aged 0 to 3 Years in Hermano Miguel Parish of the Canton of Cuenca - Lema Atiencie, Angie Estefanía (2025)
Objective: Oral hygiene in children aged 0 to 3 years is essential to prevent dental caries and promote healthy habits. Materials and methods: This was a quantitative, descriptive, observational and cross-sectional study. The sample consisted of 240 children aged 0 to 3 years. The information was collected through a questionnaire validated and approved by experts in the area. This instrument consisted of 16 questions about affiliation, type of oral hygiene input, frequency of tooth brushing and type of toothpaste that the father uses on the child. Data was processed by the statistical software SPSS in its version 26. Results: TMost of the sample was made up of girls (51.7%). The most reported frequency of tooth brushing was twice a day (48.8%). The most used fluoride toothpaste is 1000-1100 PPM (35.8%). 40% of one-year-old children use the amount of toothpaste equivalent to 1 grain of raw rice. The most common daily brushing was twice a day (54.8%) in households with incomes below $400. Conclusion: Most of the children aged 0-3 years in the Hermano Miguel Parish brush their teeth twice a day and use fluoride toothpaste of 1000-1100 PPM. Conclusion: Giomer Beautifil II presented the highest surface hardness, while Tetric N-Ceram Bulk Fill resin achieved the highest compressive strength. Conversely, Alkasite Cention-N obtained the lowest values for both mechanical properties.